2015
DOI: 10.7727/wimj.2014.361
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Inequality in Professionally Administered Topical Fluoride among Mexican Schoolchildren

Abstract: Objective: To identify and characterize socioeconomic inequalities in professionally administered topical fluoride treatment to schoolchildren. Methods: One thousand six hundred and forty-four schoolchildren [6 to 13 years of age, mean 9.06 ± 2.02; years 50.9% boys] were included in a cross-sectional study. Using questionnaires directed to mothers/guardians, we collected sociodemographic, socioeconomic and dental variables. The dependent variable was at least one professional application of topical fluoride by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
1
5
1
Order By: Relevance
“…Previous studies have confirmed that self-care devices such as brushing teeth with toothpaste, flossing or using mouthwash increase the likelihood of using dental services for regular recall examination or receiving preventive treatments 12 14 19 32 34 35. The findings of this study reveal that, although individuals who use self-care devices are more likely to visit dental offices seeking both types of services, the effect of this variable is greater on preventive services.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Previous studies have confirmed that self-care devices such as brushing teeth with toothpaste, flossing or using mouthwash increase the likelihood of using dental services for regular recall examination or receiving preventive treatments 12 14 19 32 34 35. The findings of this study reveal that, although individuals who use self-care devices are more likely to visit dental offices seeking both types of services, the effect of this variable is greater on preventive services.…”
Section: Discussionsupporting
confidence: 65%
“…The mechanisms involved are likely a combination of healthy behaviours, healthy lifestyles and improved access to medical care 29. In several studies carried out around the world, it has been observed that variables related to socioeconomic status are good predictors of DHSU, such as education level 12 29 30 33 35 36. Mothers’ education level was associated with using dental services in our study, which presumably indicates that lower access to knowledge and poorer understanding of oral health may be associated with unhealthy behaviours; it is unclear whether such scenario leads to lower engagement in preventive and curative treatment.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Thereby, Casanova-Rosado et al, 51 Manfredini et al, 52 and Wieckiewicz et al 53 recommend the use of validated tools such as the RDC/TMD in order to increase the level of reliability among studies in children and adolescents. This tool has been used as a method of diagnosis for both children and adults.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the pain experience is a good risk indicator of the existence of dental disease. In México, too is reported that preventive dental services utilisation is very low (20).…”
Section: Discussionmentioning
confidence: 99%